Preparation method of honeycomb porous zinc aluminate ceramic
By using bauxite and zinc oxide as the main raw materials and combined with soluble starch as pore agents, honeycomb porous zinc aluminate ceramics with high porosity, low volume density, high flexural resistance and compressive strength, the problems of high cost and poor performance in the prior art are solved, and efficient and low-cost porous ceramic preparation are achieved.
Patent Information
- Application Number
- CN202411927496.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the preparation of porous zinc aluminate ceramics is costly and has poor performance, making it difficult to achieve a honeycomb pore structure while maintaining high strength.
Bauxite is used as the aluminum source and zinc oxide as the zinc source, combined with soluble starch as the pore-forming agent, and honeycomb porous zinc aluminate ceramics are prepared by wet ball milling, drying, sieving, pressing molding and sintering.
The honeycomb porous zinc aluminate ceramic with high porosity, low volume density, high flexural resistance and compressive strength was successfully prepared, which reduced production costs and broadened its application range.
Smart Images

Figure CN119707523A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst carriers, filter materials and thermal insulation materials in inorganic chemical industry, and specifically relates to a preparation method of honeycomb porous zinc aluminate ceramics. Background Art
[0002] Porous ceramics are a new type of ceramic material with regular or irregular pore structures. Due to their unique properties, they are widely used in environmental protection, chemical industry, biomedical field, aerospace field and heat exchange field. Among them, porous zinc aluminate ceramics can be used as filter materials due to their excellent properties. Their performance characteristics are mainly as follows: 1. High specific surface area: Porous zinc aluminate ceramics have a large number of tiny pores, which greatly increase the specific surface area of the material, enabling it to effectively adsorb and capture particulate matter. 2. Good chemical stability: Zinc aluminate ceramics have good chemical stability in both acid and alkaline environments, are not easily corroded, and are suitable for filtering various chemicals. 3. High temperature resistance: Porous zinc aluminate ceramics can withstand high temperature environments and are suitable for filtering high temperature gases or liquids, such as flue gas filtration emitted by industrial furnaces. 4. High mechanical strength: Zinc aluminate ceramics have high mechanical strength, can withstand certain pressure and impact, and are suitable for continuous operation in industrial environments. Therefore, these characteristics of porous zinc aluminate ceramics make it an ideal filtering or adsorption material, suitable for various occasions requiring efficient and stable filtration. Pores bring many benefits to porous ceramics, but the presence of pores reduces the effective bearing area of the material, resulting in decreased mechanical strength and durability, and increased risk of fracture; cracks are more likely to occur during rapid temperature changes, reducing thermal shock resistance; too many pores or too large pore sizes may cause the material to be too permeable, which may reduce filtration efficiency and allow fine particles to pass through the filter material, making it unsuitable for applications that require high sealing. Therefore, the morphology and size of the pores can be changed through the preparation and sintering processes of porous ceramics.
[0003] At present, there is no report on the use of bauxite as an aluminum source and starch as a pore-forming agent to prepare honeycomb porous zinc aluminate ceramics, but there are some reports on the preparation of porous zinc aluminate. For example, a Chinese patent (publication number: CN 111205080A) discloses a high-strength zinc aluminate porous ceramic and a preparation method thereof, which uses zinc aluminate nanorods as the main raw material, SiO2 nanoparticles as filler, and anhydrous ethanol as a dispersant, and is prepared by ball milling the mixed materials, pouring into a graphite mold, and sintering at 1000-1200°C for 2-8 minutes. A Chinese patent (publication number: CN 109574650A) proposes a preparation method for a highly transparent porous zinc aluminate ceramic, which uses basic zinc carbonate and aluminum-containing compounds as the main raw materials, LiF as a sintering aid and pore-forming agent, and is prepared by mixed ball milling, drying and sieving, isostatic pressing, and sintering at 1450-1650°C for 2-4 hours. The above preparation methods all have the problems of high cost for preparing porous zinc aluminate and poor performance of porous zinc aluminate. Summary of the invention
[0004] In view of the high cost of preparing zinc aluminate ceramics in the prior art, the present invention proposes a method of preparing honeycomb porous zinc aluminate ceramics using mineral bauxite as an aluminum source and soluble starch as a pore-forming agent, which has the advantages of high porosity, low bulk density, high flexural and compressive strength, good honeycomb pore structure, etc. The porous zinc aluminate ceramics prepared by the technical solution of the present invention can reduce production costs, have a honeycomb pore structure while maintaining high strength, and can also reduce energy consumption and broaden its application range.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a honeycomb porous zinc aluminate ceramic, using bauxite and zinc oxide as main raw materials and soluble starch as a pore-forming agent, comprising the following steps:
[0007] Step 1, weighing bauxite and zinc oxide according to mass percentage;
[0008] Step 2, wet ball milling the two powders in step 1;
[0009] Step 3, drying the ball-milled slurry;
[0010] Step 4, grinding and sieving the dried bulk powder to obtain a mixed powder;
[0011] Step 5, weighing the mixed powder and soluble starch according to mass percentage, grinding and mixing;
[0012] Step 6, weighing the powder in step 5 and putting it into a mold to press it into shape;
[0013] Step 7, sintering the pressed sample, and obtaining porous zinc aluminate ceramics after cooling.
[0014] Furthermore, in step 1, the mass percentages of bauxite and zinc oxide are 20% to 80% and 80% to 20% respectively.
[0015] Furthermore, the Al2O3 content of the bauxite is 40% to 80%, the SiO2 content is 4.0% to 10.0%, the TiO2 content is 2% to 4%, the Fe2O3 content is 1.0% to 2.5%, the CaO content is 0.2% to 0.8%, the MgO content is 0.2% to 0.6%, and the ignition loss is 10.5% to 15%. The zinc oxide is analytically pure, and the ZnO content is ≥99.0%.
[0016] Bauxite is a mineral composed mainly of aluminum hydroxide and oxide, which is the main raw material for extracting aluminum metal and other aluminum compounds. Bauxite is an abundant natural resource, relatively cheap and easy to mine, so using it as an aluminum source can reduce production costs. The chemical composition of bauxite is mainly aluminum oxide (Al2O3) and water, and also contains small amounts of iron oxide (Fe2O3), silicon dioxide (SiO2), titanium oxide (TiO2) and other impurities. The impurity components in bauxite can act as a sintering aid in some cases, helping to improve certain properties of the final product, such as sinterability, density and mechanical strength. Therefore, bauxite is suitable as an aluminum source for the preparation of porous zinc aluminate ceramics.
[0017] Furthermore, the wet ball milling in step 2 is specifically as follows: adding 50% of the total mass of the two powders in deionized water, using agate beads as the ball milling medium, rotating at 200 to 600 r / min, and milling for 3 to 7 hours.
[0018] Furthermore, the drying temperature in step 3 is 60-100°C.
[0019] Further, the 60-mesh sieve is used for screening in step 4.
[0020] Furthermore, in step 5, the mass percentages of the mixed powder and the soluble starch are 95% to 50% and 5% to 50% respectively.
[0021] Furthermore, in step 6, the pressure of the pressing molding is 10 to 50 MPa, and the holding time is 20 to 40 seconds.
[0022] Furthermore, in step 7, the sintering temperature is 1000-1400° C., the heating rate is 5° C. / min, and the holding time is 2-5 hours.
[0023] The invention also provides a honeycomb porous zinc aluminate ceramic prepared by the preparation method.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention uses mineral bauxite, which is rich in raw material sources and low in cost, as an aluminum source, zinc oxide as a zinc source and soluble starch as a pore-forming agent to successfully prepare honeycomb porous zinc aluminate ceramics. The preparation process is simple and easy to operate, and it is easy to achieve large-scale production. This technology not only realizes the preparation of porous zinc aluminate ceramics using mineral bauxite, greatly reducing the production cost, but also the impurities contained in the bauxite itself can be used as a sintering aid to improve its structure and performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a scanning electron microscope image of Example 1;
[0027] Figure 2 is a scanning electron microscope image of Example 2;
[0028] Figure 3 is a scanning electron microscope image of Example 3;
[0029] Figure 4 is a scanning electron microscope image of Example 4;
[0030] Figure 5 This is a scanning electron microscope image of Example 5. DETAILED DESCRIPTION
[0031] In order to further illustrate the technical solution of the present invention, the present invention is further described below through embodiments.
[0032] The raw materials of the present invention are: bauxite, zinc oxide and soluble starch. The bauxite has an Al2O3 content of 40% to 80%, a SiO2 content of 4.0% to 10.0%, a TiO2 content of 2% to 4%, a Fe2O3 content of 1.0% to 2.5%, a CaO content of 0.2% to 0.8%, a MgO content of 0.2% to 0.6%, and a loss on ignition of 10.5% to 15%.
[0033] Embodiment 1:
[0034] The preparation method of honeycomb porous zinc aluminate ceramics is as follows:
[0035] (1) Weigh 30% bauxite and 70% zinc oxide by mass.
[0036] (2) The two powders were added to deionized water (50% of the total mass of the two powders) for wet ball milling. The ball milling medium was agate beads, the ball milling speed was 200 r / min, and the ball milling time was 7 h.
[0037] (3) The ball-milled slurry was placed in a drying oven and dried at 60°C.
[0038] (4) After the slurry is dried, it is sieved through a 60-mesh sieve to obtain a mixed powder.
[0039] (5) Then weigh 90% of the mixed powder and 10% of soluble starch according to mass percentage, grind and mix for 20 minutes.
[0040] (6) The ground and mixed powder is poured into a mold and pressed into a green body on a pressure testing machine with a molding pressure of 10 MPa and a holding time of 40 s.
[0041] (7) The pressed green body is placed in a silicon-molybdenum rod box furnace and calcined at 1100°C with a heating rate of 5°C / min and a holding time of 5 h to obtain porous zinc aluminate ceramics.
[0042] Example 2
[0043] The preparation method of honeycomb porous zinc aluminate ceramics is as follows:
[0044] (1) Weigh 40% bauxite and 60% zinc oxide by mass.
[0045] (2) The two powders were added to deionized water (50% of the total mass of the two powders) for wet ball milling. The ball milling medium was agate beads, the ball milling speed was 300 r / min, and the ball milling time was 6 h.
[0046] (3) The ball-milled slurry was placed in a drying oven and dried at 70°C.
[0047] (4) After the slurry is dried, it is sieved through a 60-mesh sieve to obtain a mixed powder.
[0048] (5) Then weigh 80% of the mixed powder and 20% of the soluble starch according to mass percentage, grind and mix for 30 minutes.
[0049] (6) The ground and mixed powder is poured into a mold and pressed into a green body on a pressure testing machine with a molding pressure of 15 MPa and a holding time of 30 s.
[0050] (7) The pressed sample was placed in a silicon-molybdenum rod box furnace and calcined at 1200 °C with a heating rate of 5 °C / min and a holding time of 4 h to obtain porous zinc aluminate ceramics.
[0051] Example 3
[0052] The preparation method of honeycomb porous zinc aluminate ceramics is as follows:
[0053] (1) Weigh 50% bauxite and 50% zinc oxide by mass.
[0054] (2) The two powders were added to deionized water (50% of the total mass of the two powders) for wet ball milling. The ball milling medium was agate beads, the ball milling speed was 400 r / min, and the ball milling time was 5 h.
[0055] (3) The ball-milled slurry was placed in a drying oven and dried at 80°C.
[0056] (4) After the slurry is dried, it is sieved through a 60-mesh sieve to obtain a mixed powder.
[0057] (5) Then weigh 70% of the mixed powder and 30% of the soluble starch according to mass percentage, grind and mix for 40 minutes.
[0058] (6) The ground and mixed powder is poured into a mold and pressed into a green body on a pressure testing machine with a molding pressure of 20 MPa and a holding time of 35 s.
[0059] (7) The pressed sample was placed in a silicon-molybdenum rod box furnace and calcined at 1250°C with a heating rate of 5°C / min and a holding time of 3 h to obtain porous zinc aluminate ceramics.
[0060] Example 4
[0061] The preparation method of honeycomb porous zinc aluminate ceramics is as follows:
[0062] (1) Weigh 60% bauxite and 40% zinc oxide by mass.
[0063] (2) The two powders were added to deionized water (50% of the total mass of the two powders) for wet ball milling. The ball milling medium was agate beads, the ball milling speed was 500 r / min, and the ball milling time was 4 h.
[0064] (3) The ball-milled slurry was placed in a drying oven and dried at 90°C.
[0065] (4) After the slurry is dried, it is sieved through a 60-mesh sieve to obtain a mixed powder.
[0066] (5) Then weigh 65% of the mixed powder and 35% of soluble starch according to mass percentage, grind and mix for 35 minutes.
[0067] (6) The ground and mixed powder is poured into a mold and pressed into a green body on a pressure testing machine with a molding pressure of 30 MPa and a holding time of 40 s.
[0068] (7) The pressed sample was placed in a silicon-molybdenum rod box furnace and calcined at 1300 °C with a heating rate of 5 °C / min and a holding time of 4 h to obtain porous zinc aluminate ceramics.
[0069] Example 5
[0070] The preparation method of honeycomb porous zinc aluminate ceramics is as follows:
[0071] (1) Weigh 70% of bauxite and 30% of zinc oxide by mass.
[0072] (2) The two powders were added to deionized water (50% of the total mass of the two powders) for wet ball milling. The ball milling medium was agate beads, the ball milling speed was 600 r / min, and the ball milling time was 3 h.
[0073] (3) The ball-milled slurry was placed in a drying oven and dried at 100°C.
[0074] (4) After the slurry is dried, it is sieved through a 60-mesh sieve to obtain a mixed powder.
[0075] (5) Then weigh 60% of the mixed powder and 40% of soluble starch according to mass percentage, grind and mix for 30 minutes.
[0076] (6) The ground and mixed powder is poured into a mold and pressed into a green body on a pressure testing machine with a molding pressure of 40 MPa and a holding time of 25 s.
[0077] (7) The pressed sample was placed in a silicon-molybdenum rod box furnace and calcined at 1350°C with a heating rate of 5°C / min and a holding time of 3 h to obtain porous zinc aluminate ceramics.
[0078] The properties of the porous zinc aluminate ceramics prepared in Examples 1 to 5 are compared in Table 1.
[0079] Table 1 Comparison of properties of porous zinc aluminate ceramics prepared in Examples 1 to 5
[0080]
[0081] It can be seen from Table 1 that with the gradual increase in the amount of starch added, the volume density, flexural strength and compressive strength of the porous zinc aluminate ceramics gradually decreased, while the porosity gradually increased. The increase in porosity is related to the increase in the amount of soluble starch added.
[0082] The scanning electron microscope images of the porous zinc aluminate ceramics prepared in Examples 1 to 5 are as follows: Figures 1 to 5 As shown. It can be seen that as the amount of starch added gradually increases, the pores formed also gradually increase. Figure 1 and Figure 2 The pores are irregular. Figure 3 , Figure 4 and Figure 5 Initially it has a honeycomb pore structure.
[0083] The above shows and describes the main features and advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0084] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a honeycomb porous zinc aluminate ceramic, characterized in that: The following steps are involved: Step 1, weighing bauxite and zinc oxide according to mass percentage; Step 2, wet ball milling the two powders in step 1; Step 3, drying the ball-milled slurry; Step 4, grinding and sieving the dried bulk powder to obtain a mixed powder; Step 5, weighing the mixed powder and soluble starch according to mass percentage, grinding and mixing; Step 6, weighing the powder in step 5 and putting it into a mold to press it into shape; Step 7, sintering the pressed sample, and obtaining porous zinc aluminate ceramics after cooling.
2. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: In the step 1, the mass percentages of bauxite and zinc oxide are 20% to 80% and 80% to 20% respectively.
3. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 2, characterized in that: The bauxite has an Al2O3 content of 40% to 80%, a SiO2 content of 4.0% to 10.0%, a TiO2 content of 2% to 4%, a Fe2O3 content of 1.0% to 2.5%, a CaO content of 0.2% to 0.8%, a MgO content of 0.2% to 0.6%, and a loss on ignition of 10.5% to 15%.
4. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: The wet ball milling in step 2 specifically includes: adding 50% of the total mass of the two powders in deionized water, using agate beads as the ball milling medium, rotating at 200-600 r / min, and milling for 3-7 hours.
5. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: The drying temperature in step 3 is 60-100°C.
6. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: In step 4, a 60-mesh sieve is used for screening.
7. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: In step 5, the mass percentages of the mixed powder and the soluble starch are 95% to 50% and 5% to 50% respectively.
8. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: The pressure of the pressing in step 6 is 10-50 MPa, and the holding time is 20-40 s.
9. The method for preparing a honeycomb porous zinc aluminate ceramic according to claim 1, characterized in that: In step 7, the sintering temperature is 1000-1400° C., the heating rate is 5° C. / min, and the holding time is 2-5 hours.
10. A honeycomb porous zinc aluminate ceramic prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of porous zinc aluminate ceramics with high wave permeability
CN109574650A
High-strength zinc aluminate porous ceramic and preparation method thereof
CN111205080A